Reimagining Civil Society Collaborations in Development : Starting from the South. - van Wessel, Margit. (Taylor & Francis Group, 2023)
This book will be an important contribution to researchers and practitioners working on innovation in development and civil society. This book re-imagines and re-centers Civil Society collaborations in development, offering Southern-centred ways of understanding and developing relations, roles, and processes, in theory and practice.